The Effect of Continous or Intermittent Calcitonin in the Treatment of Postmenopausal Osteoporosis - F. Taşçıoğlu; C. Öner; O. Armağan (Galenos Yayinevi, 2002)
The aim of this study was to compare the efficacy of continuous and intermittent salmon calcitonin in the treatment of postmenopausal osteoporosis. Sixty-eight women with postmenopausal osteoporosis were randomized to 2 treatment groups. The first group consisting of 33 patients received nasal salmon calcitonin 200 IU/day. Thirty-five patients in the second group were treated with 200 IU of nasal SCT daily for 5 days with a subsequent pause of 2 days. All received a daily supplement of 1000 mg calcium. Both treatment regimen were applied for 12 months. The effect of nasal calcitonin on bone mineral density (BMD)was investigated by DEXA. Serum ALP, Ca and P levels and urinary Ca excretion were assessed before the treatment and at the end of 12 months. Serum ALP levels decreased mildly, but in a statistically significant manner in both groups ( p< 0.05). There was no significant differences for the other biochemical parameters(p> 0.05). There was a significant increase above baseline in the BMD of the lumbar spine, trochanteric region and Ward's triangle in both groups (p< 0.01, p< 0.05 and p<0.05 respectively). In both groups no significant change was observed in femur neck BMD (p> 0.05). This study indicates that both continuous and intermittent SCT at a dosage of 200 IU/day are effective in the treatment of postmenopausal osteoporosis .